التعويض عن الضرر في الفقه الإسلامي والقانون الفلبيني : دراسة تحليلية مقارنة - أحمد، بدرالدين فاجيمانان (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2014)
This study deals comparatively with the issue of compensation for damage in Islamic Jurisprudence and Philippine law. Accordingly, the researcher examines certain basic concepts and terms related to compensation (such as obligation, liability and guarantee). Then the concept of damage and its causes, conditions and types, as well as the concept of compensation and its kinds, the criteria for assessing it, and the rules governing compensation for damage are discussed. These have been done in the context of contrasting and comparing the positions of both Islamic jurisprudence and Philippine law and its applications regarding the different aspects of the issue under consideration. The researcher has employed inductive, analytical and comparative methods. After collecting the relevant data from different sources, he analyzed and examined them in order to determine what is preponderant therein by looking into the supporting evidence of the views of both classical and contemporary Muslim jurists and legal scholars and then contrasting them with the articles and provisions of the old and new (amended) Philippine civil code pertaining to compensation for damage. Based on that, the study has shown that Islamic jurisprudence and Philippine law are in agreement on compensation for material damage in tort liability. However, they differ on its basis; thus, while the Philippine law considers fault or negligence as the basis for compensation for damage, Islamic jurisprudence considers that the damage itself is basis. The study has also shown that the Philippine civil law has been influenced, though indirectly, by Islamic (especially Maliki) jurisprudence in certain matters of compensation for damage; this influence has mostly taken place through the Spanish law that had been influenced by Islamic jurisprudence in the land of Andalusia. This can be seen in the question of abstention from the principle of obligation in “Maliki Jurisprudence” in the fulfillment of promise or contractual liability based on direct cause, and its counterpart “the obligation in compensation for tort liability” in Spanish – Philippine civil law.